1872 Terr. of Mont. Laws 562 - (:unkn) unknown (My University, 1872)
Ch. 63, § 1: It shall be the duty of any keeper of the arsenal, military stores, ammunition, arms and ordnance belonging to this territory . . . to report to the governor in writing the amount of such military stores and ammunition, and a list and description of such arms and ordinance in his possession and within his knowledge
Keywords: ARMED FORCES